Valuation Waterfalls for Gaming Company In-App Purchases: An Integrated Strategic Approach - Anjali Kale (Emerging Frontiers Library for The American Journal of Management and Economics Innovations, 2025)
In-app purchases (IAPs) have become the primary revenue stream in the mobile gaming industry, with complex valuation waterfalls determining how revenue flows through platform fees, publisher shares, developer royalties, and marketing costs. Accurate modelling of these waterfalls is essential for financial planning, investor reporting, and M&A negotiations. This research article introduces a structured framework for analysing IAP valuation waterfalls, focusing on gross-to-net revenue flows, platform commissions, bundling, and discounts. Traditional valuation models often fail to capture key dynamics like lifetime value (LTV), churn, and monetization cycles. To address this, we propose an enhanced approach that integrates user behavior analytics, cohort analysis, and probabilistic forecasting. The paper examines stakeholder incentives developers, publishers, platforms, and investors and uses real-world examples to show how different pricing models (e.g., loot boxes, subscriptions) impact waterfall efficiency. Comparative insights from markets like the U.S., China, and South Korea underscore the global relevance of this method. A practical guide and spreadsheet template support implementation, making the framework useful for CFOs and strategic planners.